Enhancing Access and Usage of Earth Observations in Environmental Decision-Making in Eastern and Southern Africa Through Capacity Building - Shukla, Shraddhanand; Macharia, Denis; Husak, Gregory J.; Landsfeld, Martin; Nakalembe, Catherine Lilian; Blakeley, S. Lucille; Adams, Emily Caitlin; Way-Henthorne, Juliet (Frontiers in Sustainable Food Systems, 2021)
Major strides have been made in the development of remote sensing, reanalysis, and model-based earth observations (EOs), which can be used for long-term climate variability mapping, as well as real-time environmental monitoring and forecasting. Such EOs are particularly valuable for environmental decision-making (e.g., for environmental resources management and disaster mitigation) in the Eastern and Southern Africa (E & SA) region, where ground-based EOs are sparse. Nonetheless, operational application of those EOs to inform decision-making in the region remains limited. This paper reports on a recently concluded (as of June 2019) NASA SERVIR-supported Applied Science Team project that contributed to the uptake of EO applications to inform decision-making in this region. This project was conducted in close collaboration with the Regional Centre for Mapping of Resources for Development (RCMRD)—the NASA SERVIR regional hub in E & SA, one of the most prominent environmental service providers in this region since 1975, which is mandated to provide services to 20 countries in the region. The capacity-building efforts were conducted by leveraging from RCMRD’s existing environmental service capacity, their long experience in capacity building in the region, and their extensive network of regional partners, with the goal of increasing RCMRD and their regional partners’ ability to uptake EOs to enhance their environmental services and, hence, improve the environmental decision-making process. This project utilized two primary avenues for capacity building and enhancing the uptake of EOs in the region: (1) Transfer of technology—Transition and implementation of web-based tools to RCMRD to allow easy processing and visualization of EOs and (2) Capacity training—training of representatives from regional and national environmental service agencies in EO application based on targeted case studies. Here, we describe these capacity-building efforts, provide specific examples to demonstrate the benefits of those efforts in terms of enhanced uptake of EOs, and provide recommendations for furthering the uptake of EOs in the region and beyond.